Thermodynamical Study of Poly(n-hexyl methacrylate) with Some Solvents by Inverse Gas Chromatography - Yazici, Ozlem; Sakar, Dolunay; Cankurtaran, Ozlem; Karaman, Ferdane (WILEY, 2011)
The retention volume diagrams of ethyl acetate, isobutyl acetate, tert-butyl acetate, benzene, n-hexane, n-heptane, n-octane, acetone, chloroform, and acetonitrile on the poly(n-hexyl methacrylate) (PHMA) were plotted at temperature ranges from 333 to 393 K by inverse gas chromatography technique. Some polymer-solvent thermodynamic interaction parameters, such as weight fraction activity coefficient, Omega(infinity)(1), Flory-Huggins, chi(infinity)(12), hard-core, chi(12)*, and some exchange parameters such as effective energy, X-eff, enthalpy, X-12, and entropy, Q(12), were determined for studied solvents at infinite dilution of PHMA at temperatures mentioned above. Then the partial molar heat, Delta(H) over bar (s)(1), and free energy, Delta(G) over bar (s)(1), of sorption as well as the partial molar heat, Delta(H) over bar (infinity)(1), and free energy, Delta(G) over bar (infinity)(1), of mixing at infinite dilution were determined. In addition, the solubility parameter of PHMA, delta(2), was determined as 8.8 (cal/cm(3))(1/2) at room temperature by extrapolation of the values of solubility parameters from studied temperatures to 298 K. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1815-1822, 2011
Keywords: poly (n-hexyl methacrylate); polymer-solvent interactions; inverse gas chromatography; solubility parameter; CHAIN MOLECULE LIQUIDS; EQUATION-OF-STATE; STATISTICAL THERMODYNAMICS; POLYSTYRENE SOLUTIONS; POLYMER; PARAMETERS; MIXTURES; Polymer Science